2015
DOI: 10.1007/s11239-015-1235-1
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative INR and postoperative major bleeding and mortality: A retrospective cohort study

Abstract: Little research has been done on the current cut-off international normalized ratio (INR) value of 1.5 for patients undergoing surgery. The objectives of this study are to assess the association between INR and postoperative major bleeding and mortality in patients undergoing surgery and to identify an ideal pre-operative INR for surgical patients. We analyzed data from the American College of Surgeons' National Surgical Quality Improvement Program database between 2008 and 2011 (636,231 patients). The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 25 publications
2
35
0
Order By: Relevance
“…Tamim et al reported increased risk for major bleeding and mortality among general surgery patients with a preoperative INR greater than 1.10 and 1.13, respectively. 2 Others have examined postoperative bleeding in general surgery but have not reported an elevated bleeding risk. [3][4][5] A review by Segal et al concluded that there is inadequate evidence to conclude that an elevated INR predicts postoperative bleeding among invasive procedures.…”
mentioning
confidence: 99%
“…Tamim et al reported increased risk for major bleeding and mortality among general surgery patients with a preoperative INR greater than 1.10 and 1.13, respectively. 2 Others have examined postoperative bleeding in general surgery but have not reported an elevated bleeding risk. [3][4][5] A review by Segal et al concluded that there is inadequate evidence to conclude that an elevated INR predicts postoperative bleeding among invasive procedures.…”
mentioning
confidence: 99%
“…This is notably different from the commonly accepted INR value of 1.5 as safe for surgical intervention . Tamim et al questioned this commonly accepted INR value of 1.5 and found that a high preoperative INR was associated with postoperative bleeding and an increased 30‐day mortality for all surgical specialties. The group determined that an INR of 1.1 and 1.13 minimized bleeding and mortality, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…However, there is limited data describing the impact of hypocoagulability or prolonged bleeding states in pancreas surgery. Recent studies have suggested that a patient's coagulation profile, as defined by the international normalized ratio (INR) and partial thromboplastin time (PTT), is associated with poor surgical outcomes including 30‐day mortality . Liver dysfunction from cholestasis or chemotherapy is a common occurrence prior to pancreas surgery and may factor into prolonged bleeding times.…”
Section: Introductionmentioning
confidence: 99%
“…predictive value of INR for postoperative complications, with several studies suggesting a poor predictive and others suggesting that even small increases in INR raise the risk of major bleeding and mortality. [4][5][6][7] In an effort to clarify the effect of INR on outcomes in total joint arthroplasty, Rudasill et al studied 21,239 patients undergoing elective primary TKA and found a stepwise increase in risk for bleeding, infection, and mortality. 7 This challenges several studies that suggest elevated INR has no effect on postoperative complications in orthopaedic surgery.…”
mentioning
confidence: 99%
“…1,3 However, despite the widespread implemen-tation of these guidelines, the predictive value of INR following joint arthroplasty remains controversial. [4][5][6][7][8] In the current literature, most studies assessing the connection between elevated INR and the risk of perioperative bleeding have analyzed patients undergoing neurologic, cardiac, and general surgeries, rather than orthopaedic surgery. 9 Furthermore, the current literature presents mixed conclusions for the…”
mentioning
confidence: 99%